2015
DOI: 10.1016/j.rpped.2014.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Aditivo homólogo para a alimentação do recém‐nascido pré‐termo de muito baixo peso

Abstract: OBJECTIVE: To develop a homologous human milk supplement for very low-birth weight infant feeding, using an original and simplified methodology, to know the nutritional composition of human milk fortified with this supplement and to evaluate its suitability for feeding these infants. METHODS: For the production and analysis of human milk with the homologous additive, 25 human milk samples of 45mL underwent a lactose removal process, lyophilization and then were diluted in 50mL of human milk. Measurements of la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
1
4
0
1
Order By: Relevance
“…The lipid content of the HMB and HMCI samples in the present study was higher than that of the formulations reported by Grance et al (2015). The lipid content as reported by present study was 2.59 g/100 ml in HMB and 4.03 g/100 ml in HMCI samples, while the lipid content reported by Grance et al was 1.49 g/100 ml in human milk without a homologous additive, and 2.91 g/100 ml in human milk with a homologous additive [ 30 ].…”
Section: Discussionsupporting
confidence: 42%
“…The lipid content of the HMB and HMCI samples in the present study was higher than that of the formulations reported by Grance et al (2015). The lipid content as reported by present study was 2.59 g/100 ml in HMB and 4.03 g/100 ml in HMCI samples, while the lipid content reported by Grance et al was 1.49 g/100 ml in human milk without a homologous additive, and 2.91 g/100 ml in human milk with a homologous additive [ 30 ].…”
Section: Discussionsupporting
confidence: 42%
“…That same research group has recently improved the formulation method of the powder additive by minimizing the risks of the elaboration and handling processes of HM by simplifying the method to lactose reduction and lyophilization alone. The partial removal of lactose is justified by the control of osmolality of HM strengthened with the powdered additive, which increases tolerance by preterm infants, minimizing the risk of NEC [3940]. In the present study, the proposed simplified method consists of lyophilization without lactose reduction, and it is important to highlight that the concentrated HM after the addition of the lyophilizate maintained an acceptable osmolality according to the values tolerated by VLBW infants.…”
Section: Discussionmentioning
confidence: 98%
“…However, despite substantial variation, the osmolality of human milk remained within the recommended values reported in the literature 15,17,18,21 for safe use, suggesting that rice cereal supplementation is a potential therapeutic feeding strategy for infants with mild or moderate oropharyngeal dysphagia. Human milk is a protective factor for infants with dysphagia because until approximately 6 months of age, the Anova test 0% vs. 2%, p = 0.000 2% vs. 5%, p = 0.033 0% vs. 3%, p = 0.000 2% vs. 7%, p = 0.006 0% vs. 5%, p = 0.000 3% vs. 5%, p = 0.104 0% vs. 7%, p = 0.000 3% vs. 7%, p = 0.024 2% vs. 3%, p = 0.989 5% vs. 7%, p = 0.974 amylase enzyme involved in the hydrolysis of the starch is lacking or present in small quantities; this enzyme is obtained via human milk which aids in the digestion of the starch 24 .…”
Section: Discussionmentioning
confidence: 63%
“…Thus, variations observed in human milk may be associated with the presence of the amylase enzyme. Amylase in human milk can cause the hydrolysis of starch and consequently can result in a concentration-and timedependent increase in osmolality 21 . The differences observed among the infant formula samples were associated with the concentration of thickener, because the differences began to be noticed when the concentration of the thickener varied.…”
Section: Discussionmentioning
confidence: 99%